2018
DOI: 10.1021/acs.langmuir.8b02832
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Molecular Sheets Woven by Water Cavities in Hydrophobic Slit Nanospaces

Abstract: Despite extensive research over the last several decades, the microscopic characterization of topological phases of adsorbed phenol from aqueous solutions in carbon micropores (pore size < 2.0 nm), which are believed to exhibit a solid and quasi-solid character, has not been reported. Here, we present a combined experimental and molecular level study of phenol adsorption from neutral water solutions in graphitic carbon micropores. Theoretical and experimental results show high adsorption of phenol and negligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…4 In recent years, superhydrophobic surfaces have drawn great attention in theoretical research and potentials in practice. 5,6 It has been reported that the superhydrophobic surfaces present unique properties, such as self-cleaning, oil−water separation, antibacteria, drag reduction, luminescent solar concentrators, and corrosion resistance. 7−15 However, superhydrophobic surfaces can be easily destroyed under extreme environments such as acid rain and etchant solutions, leading to limited applications in industry, especially anticorrosive fields, because of their poor stability of superhydrophobic coating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In recent years, superhydrophobic surfaces have drawn great attention in theoretical research and potentials in practice. 5,6 It has been reported that the superhydrophobic surfaces present unique properties, such as self-cleaning, oil−water separation, antibacteria, drag reduction, luminescent solar concentrators, and corrosion resistance. 7−15 However, superhydrophobic surfaces can be easily destroyed under extreme environments such as acid rain and etchant solutions, leading to limited applications in industry, especially anticorrosive fields, because of their poor stability of superhydrophobic coating.…”
Section: Introductionmentioning
confidence: 99%
“…Under further investigation, their superior performance of functional surface is attributed to the typical superhydrophobic characteristic with water contact angles (WCAs) of more than 150° and rolling angles less than 10° . In recent years, superhydrophobic surfaces have drawn great attention in theoretical research and potentials in practice. , It has been reported that the superhydrophobic surfaces present unique properties, such as self-cleaning, oil–water separation, antibacteria, drag reduction, luminescent solar concentrators, and corrosion resistance. However, superhydrophobic surfaces can be easily destroyed under extreme environments such as acid rain and etchant solutions, leading to limited applications in industry, especially anticorrosive fields, because of their poor stability of superhydrophobic coating. It is therefore urgent to explore the corrosion mechanism or protection mechanism when such surfaces are immersed into various corrosive media .…”
Section: Introductionmentioning
confidence: 99%